Teknik Pengemasan Jagung Pipil untuk Meminimumkan Kadar Aflatoksin - Dede Risanda; Emmy Darmawati; Meity Suradji Sinaga (PERTETA, 2018)
AbstractThe application of hermetic storage, which is a type of modified atmosphere, effectively reduced the growth of Aspergillus flavus during storage and therefore limit the aflatoxin production. However, its relatively high cost isa major obstacle for its adoption by smallholder farmers and traders. The preparation of two layers of HDPE and polypropylene plastic packaging that is expected to limit the aflatoxin production and prevent the mold growthduring storage. The experimental design used in this study was a completely randomized factorial design. The first factor consisted of three levels: plastic bag (J0), multi-layered plastic packaging composed of plastic bag and hermetic GrainPro bag (J1), and multi-layered plastic packaging composed of plastic bag, high density polyethylene (HDPE), and polypropylene bag (J2). Furthermore, the second factor comprised two levels: without inoculation (M0) and with inoculation (M1). The maize grains that had been stored for three months in J1 and J2packaging at 12-13% moisture levels has been able to maintain material moisture content remains low. In these two packaging, the percentage of aflatoxin infection was around 2% during three months. On the other hand, the maize grains that had been stored in J1 and J2 packaging at 17-18% moisture content showed that the material moisture content remains high during storage. The fungal infection percentage attain 3-17% in both two types of packaging. Storing the maize grains in J2 packaging with high moisture levels during three months at risk of being contaminated by aflatoxin and seed fermentation.AbstrakPenyimpanan jagung melalui modifikasi atmosfer yang terbentuk pada kemasan hermetik telah mampu menghambat pertumbuhan cendawan dan produksi aflatoksin. Namun, kemasan hermetik merupakan produk impor dan harganya relatif mahal untuk diterapkan di tingkat petani dan pedagang pengumpul. Penyusunan dualapis kemasan berbahan plastik HDPE dan polipropilen diharapkan mampu menekan produksi aflatoksin dan menghambat pertumbuhan cendawan selama penyimpanan. Rancangan percobaan yang digunakan adalah rancangan acak lengkap faktorial. Faktor pertama adalah jenis kemasan dengan 3 taraf, yaitu (J0) karung plastik, (J1) kemasan berlapis yang tersusun dari karung plastik+plastik hermetik GrainPro, dan (J2) kemasan berlapis yang tersusun dari karung plastik+plastik HDPE+plastik polipropilen. Faktor kedua adalah inokulasi sumber inokulum dengan 2 taraf, yaitu (M0) tanpa inokulasi sumber inokulum, dan (M1) dengan inokulasi sumberinokulum. Jagung pipil yang telah disimpan selama 3 bulan pada kemasan J1 dan J2 pada kadar air rendah (12-13%) telah mampu mempertahankan kadar air bahan tetap rendah. Di kedua jenis kemasan tersebut, persen infeksi cendawan masih sekitar 2% setelah disimpan selama 3 bulan. Sementara itu, penyimpanan jagung pipil pada kemasan J1 dan J2 pada kadar air tinggi (17-18%) menunjukkan bahwa kadar air bahan tetap tinggi selama penyimpanan. Persen infeksi cendawan mencapai 3-17% pada kedua jenis kemasan tersebut. Penyimpanan jagung pipil dengan kemasan J2 pada kadar air tinggi selama 3 bulan beresiko tercemar aflatoksin serta biji mengalami fermentasi.